MISTERUL ȘI SENSUL MORȚII ÎN CREȘTINISM - CHIVARI, Alex - Dominic (Studia Universitatis Babeș-Bolyai Theologia Graeco-Catholica Varadiensis, 2024)
The Mistery and Meaning of Death in Christianity. What is our hope as Christians? What are we looking forward to? What future does God have in store for us after we die? Will it involve this beautiful earth as well as all of creation? To raise these kinds of questions is to ask ourselves questions about eschatology, about realities and the end times. Given that, as we said above, the Christian faith is essentially eschatological, we eagerly await the coming of the Eschaton, having the hope of the coming of the age of salvation, of the establishment of the Kingdom of Heaven. Eschatology should occupy a central place in our Christian faith, because without a belief in the realities of the future, we have no hope.